Good Corporate Governance: Three Ways of Moderating Infrastructure Companies Should Be Aware - Arry Eksandy (International Journal of Social Science and Business, 2024)
This study aims to analyze the interaction between good corporate governance with profitability, free cash flow, and company size against fluctuating dividend policies. This research was conducted on infrastructure companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 period. The research sample consisted of 21 companies with a total of 85 observational data obtained through the purposive sampling method. Data analysis was carried out using linear panel data analysis techniques and using the Eviews 12 application for data processing. The results of this study show that profitability has a positive influence on dividend policy, while free cash flow does not have a significant influence on dividend policy, and company size has a negative influence on dividend policy. In addition, this study also found that good corporate governance can moderate the effect of profitability on dividend policy, but is unable to moderate the effect of free cash flow and company size on dividend policy. The conclusion of this study is that profitability is an important factor in determining the dividend policy of infrastructure companies. Good corporate governance also has an important role in influencing the relationship between profitability and dividend policy. However, free cash flow and company size do not have a significant effect on dividend policy. The implications of this study are the importance of infrastructure companies to pay attention to these factors in making decisions related to dividend policy, as well as the importance of implementing good corporate governance to ensure optimal dividend policy.